1998
DOI: 10.1002/mds.870130418
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical intervention for cervical disk disease in dystonic cerebral palsy

Abstract: We report five young patients with athetoid-spastic cerebral palsy who had deteriorated neurologically. Magnetic resonance imaging (MRI) was used to investigate suspected compressive cervical spine lesion. Cervical spondylosis with disk protrusions was found in all patients. Four patients underwent surgery by an anterior approach with insertion of a bone graft resulting in substantial clinical improvement. The other patient, diagnosed 8 years after onset of symptoms, was treated conservatively. The availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 15 publications
1
24
0
2
Order By: Relevance
“…Prolonged improvement of the movement disorder would be desirable in this difficult to treat group of patients. Delayed dislodgement of methylmethacrylate resulting in additional neurological deficits has been described after spinal surgery for choreoathetotic infantile cerebral palsy, 23 and, as in one of the patients discussed here, spinal stabilisation without treatment of the underlying movement disorder may not result in long term benefit. It has been debated whether anterior or posterior approaches should be preferred in spinal surgey on patients with choreoathetosis.…”
Section: Discussionmentioning
confidence: 70%
“…Prolonged improvement of the movement disorder would be desirable in this difficult to treat group of patients. Delayed dislodgement of methylmethacrylate resulting in additional neurological deficits has been described after spinal surgery for choreoathetotic infantile cerebral palsy, 23 and, as in one of the patients discussed here, spinal stabilisation without treatment of the underlying movement disorder may not result in long term benefit. It has been debated whether anterior or posterior approaches should be preferred in spinal surgey on patients with choreoathetosis.…”
Section: Discussionmentioning
confidence: 70%
“…Posteriormente se comenzaron a utilizar técnicas de descompresión y fusión anterior y/o posterior, con resultados controvertidos, pero no desalentadores 5,6,8,12,15,16 . La descompresión y fusión por vía exclusivamente anterior ha demostrado un buen resultado clínico 17 ; por otro lado en varias series, que han llevado un seguimiento a largo plazo, se ha demostrado fracaso de la artrodesis y reincidencia de los síntomas en un número importante de pacientes. Además se han reportado casos de deterioro (cifosis) de los niveles adyacentes e inestabilidad atlo-axial 12,17 .…”
Section: Discussionunclassified
“…La descompresión y fusión por vía exclusivamente anterior ha demostrado un buen resultado clínico 17 ; por otro lado en varias series, que han llevado un seguimiento a largo plazo, se ha demostrado fracaso de la artrodesis y reincidencia de los síntomas en un número importante de pacientes. Además se han reportado casos de deterioro (cifosis) de los niveles adyacentes e inestabilidad atlo-axial 12,17 . Como otra complicación, la artrodesis anterior de estos pacientes, sobre todo si es de más de un nivel, se asocia con tasas más elevadas de fracturas vertebrales y pseudoartrosis 10 .…”
Section: Discussionunclassified
“…But, laminectomy frequently caused spinal instability and consequent recurrence of symptoms in the relatively early postoperative period; subsequently, laminectomy was thought to be contraindicated in athetoid cerebral palsy 1,15,27,28) . Thereafter, anterior 21,22) and/or posterior spinal fusions of several methods have been reported, and their short-term or mid-term results do not seem unsatisfactory. However, most of the reports are small cases and long-term follow-up studies are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the reports are small cases and long-term follow-up studies are very rare. Several reports have shown that multilevel anterior decompression and fusion may lead to good clinical results if bony fusion could be obtained without such complications as significant graft extrusion and hardwarerelated complications and kyphotic deformity 21,22) . But, several physicians, who carried out the long-term followup studies, reported that considerable patients had shown recurrence of symptoms 9) .…”
Section: Discussionmentioning
confidence: 99%